Values and the need for a character education programme within the college context in the North-West Province: exploration and preliminary proposals - Freeks, F. E. (Koers, 2011)
Values and character education possess the inherent building blocks for the preservation of a healthy society. Values and character education have the potential to address moral issues in society and especially in educational institutions, such as schools, colleges and universities. One of the primary aims of values and character education is to allow students to experience life to the fullest. Values and character education could probably ensure a better life and future for South Africa?s youth.From the available literature, it is evident that society is experiencing a crisis regarding values, character and morality. The decline of human and societal values portrayed in the media has compelled the current government to initiate values education programmes in colleges and other institutions such as universities.In order to determine the values orientation among students of Further Education and Training Colleges (FET) in the North-West Province, an empirical study was done to ascertain students? opinions and the contributions of values education and character education. Semi-structured interviews were also conducted with the student council, the head of support services, as well as an official of student support services.